n Ekonomiese ondersoek van besproeiingsboerdery langs die Olifantsrivier (Vredendal), 1956-57 - Hyman, Louis George Reynolds (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.)--Stellenbosch University, 1959.